2015
DOI: 10.1128/jcm.01263-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Third-Generation-Cephalosporin-Resistant Shiga Toxin-Producing Strains of Escherichia coli O157:H7 in Japan

Abstract: cWe isolated Shiga toxin-producing Escherichia coli O157:H7 strains resistant to third-generation cephalosporins. The resistant strains harbored bla CMY-2 , a plasmid-mediated AmpC ␤-lactamase. Genotyping of isolates revealed the possible spread of this problematic bacterium. Results suggested the importance of the investigation and surveillance of enterobacteria with plasmids harboring bla CMY-2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…E. coli O157:H7 with identical PFGE pattern (100% similarity) carry different virulence genes and different drug resistance phenotypes, suggesting that the virulence and drug resistance carried by E. coli O157:H7 may be acquired or lost during the evolution and transfer of the same cluster of strains. The β-lactam-resistant E. coli O157:H7 may give β-lactam resistance to other pathogenic enterobacteria via plasmidmediated conjugation, thereby posing potential challenges in the management of their associated infectious disease in cattle (60). E. coli O157:H7 was prevalent in 2-15% population of cattle and other animals in China (47).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157:H7 with identical PFGE pattern (100% similarity) carry different virulence genes and different drug resistance phenotypes, suggesting that the virulence and drug resistance carried by E. coli O157:H7 may be acquired or lost during the evolution and transfer of the same cluster of strains. The β-lactam-resistant E. coli O157:H7 may give β-lactam resistance to other pathogenic enterobacteria via plasmidmediated conjugation, thereby posing potential challenges in the management of their associated infectious disease in cattle (60). E. coli O157:H7 was prevalent in 2-15% population of cattle and other animals in China (47).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pAmpC genes responsible for the AmpC phenotype was detected by multiplex PCR, as described by [ 8 ]. bla TEM genes were identified by sequencing, as previously described [ 9 ], and bla SHV genes were also identified by sequencing with primers designed in this study (5′-CACTCAAGGATGTATTGTGGTTATGC-3′ and 5′-GCTACGAGCCGGATAACGC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported several β‐lactamase genes, such as bla CTX‐M , bla AmpC , bla CMY‐1 , bla TEM and bla DHA‐1 in STEC serotypes O26:H11, O64, O91:H14, O106:H18, O111:H8 and O157, recovered from humans and animals; some of these β‐lactamase genes were encoded on plasmids (Arvand et al, ; Dutta et al, ; Ishii et al, ; Iweriebor et al, ; Jost et al, ; Valat et al, ). Seven O157 isolates harbouring bla CMY‐2 , obtained from clinical samples at the Osaka Prefecture, Japan, had antibiotic resistance genes encoded on a IncI1 plasmid that has high transmissibility across bacterial species (Kawahara et al, ). In Ireland, multidrug‐resistant (MDR) non‐O157 STEC isolated from cattle farms and abattoirs were found to carry Class 1 integrons with antibiotic resistance genes embedded on plasmids (Kennedy et al, ).…”
Section: Acquisition and Transmission Of Antibiotic Resistance In Ar‐mentioning
confidence: 99%
“…Seven O157 isolates harbouring bla CMY-2 , obtained from clinical samples at the Osaka Prefecture, Japan, had antibiotic resistance genes encoded on a IncI1 plasmid that has high transmissibility across bacterial species (Kawahara et al, 2015). In Ireland, multidrug-resistant were found to carry Class 1 integrons with antibiotic resistance genes embedded on plasmids (Kennedy et al, 2017).…”
Section: Acqu Is Iti On and Tr An S Miss I On Of Antib I Oti C Re Smentioning
confidence: 99%